The effect of servant leadership on self-efficacy and innovative behaviour: Verification of the moderated mediating effect of vocational calling - Yunho Ji; Hyun Joong Yoon (Administrative Sciences, 2021)
This study aimed to verify the impact of servant leadership on innovative behaviour in non-governmental organisations (NGOs). It particularly investigated the role of a mediator for self-efficacy in the relationship between servant leadership and innovative behaviour. This study defined the organisational psychology-behaviour mechanism in non-profit organisations by verifying the moderated mediating effect of vocational calling in the relationship between servant leadership, self-efficacy, and innovative behaviour. The 174 pilot samples used in this study comprised community service participants in NGOs. The analysis verified the hypothesis set through causal correlations among four variables using regression analysis and the PROCESS macro developed by Hayes. Vocational calling played a moderating role in the relationship between servant leadership and self-efficacy, and vocational calling had a conditional effect on the impact of servant leadership on innovative behaviour through self-efficacy. Meanwhile, self-efficacy fully mediated servant leadership and innovative behaviour. Based on the verification of the mechanism of organisational psychology-action, this study sought ways to develop the organisation of NGOs and improve the working environment.
Keywords: 350; innovative behavior; NGO; self-efficacy; servant leadership; vocational calling